Precision targeting for retinal motion extraction using cross-correlation with a high speed line scanning ophthalmoscope. (5th November 2015) - He, Yi; Wei, Ling; Wang, Zhibin; Yang, Jinsheng; Xiqi, Li; Shi, Guohua; Zhang, Yudong
Abstract: Evaluations to quantify the precise targeting of template features and to select template sizes for retinal motion extraction were carried out using cross-correlation with a high speed line scanning ophthalmoscope (LSO) capable of 160 frames per second. The optimal template targeting was located on a retinal vessel pattern with vessel bifurcation or vessel features occupying approximately eighty percent of the template area preferred. The optimal template size for this LSO system was 80 × 80 pixels and it was able to extract retinal motion up to 300 deg s −1 at a speed of 30 Hz. Although the optimized template size was a compromise between having enough image data on the retinal features to make matches reliably and have good temporal resolution, the optimal targeting of the template location and size described here was appropriate and effective in extracting retinal motion. In addition, the determination of cross-correlation templates could be applied to other images having similar properties; i.e., relatively small features of distinct gray levels on an otherwise fairly uniform background.